“La guerra maestra violenta”. Polemos e stasis nel pensiero di Tucidide - Piovan, Dino (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
In this paper, I intend to provide an in-depth analysis of Thucydides’ account of war in the third section of his Xyngraphé. Despite most of his early commentators accused him of certain obscurity, the notions of polemos and stasis he introduces in this text deserve to be discussed and give a number of insights into the problem of war western culture. My core argument is that there is a clear analogy between Thucydides’ concept of stasis and Weil’s reflections on totalitarianism. In this perspective, a long period of stasis leads to the rise of a party, whose goal is to take power through violence and propaganda as manipulation of language.